Front Cover: Detection of HER2+ Breast Cancer Cells using Bioinspired DNA‐Based Signal Amplification (ChemMedChem 8/2020). (16th April 2020) - Rafiee, Sarah D.; Kocabey, Samet; Mayer, Michael; List, Jonathan; Rüegg, Curzio
Abstract : The Front Cover illustrates the sensitive detection of HER2+ breast cancer cells by a DNA signal amplification circuit. Circulating cancer cells (CTC), hallmarks of metastatic cancer, are difficult to detect due to infrequent occurrence. The signal of the HER2+ cell binding antibody Trastuzumab is enhanced via a DNA hybridization chain reaction. The reaction is initiated by an initiator DNA strand, coupled to the antibody. This sequence triggers the hybridization of fluorescent hairpins, forming strongly labeled DNA constructs and allowing CTC detection by flow cytometry. Artwork by Miguel Spuch‐Calvar. More information can be found in the Communication by Sarah D. Rafiee, Samet Kocabey, Michael Mayer, Jonathan List, and Curzio Rüegg. .